Do Império à República: a vida política no município de Barra Mansa - Couto, André Luiz Faria (2016)
The thesis focuses on the political life in the city of Barra Mansa, and in general, in Paraíba‟s Valley, passing from the last two decades of Brazilian Empire trough the end of the First Republic, in 1930. This period is known by the decline of coffee plantations in this region. Theses plantations reached its peak on the third quarter of the XIX century, and for the consequent economic configuration, the livestock development and the first industries showing up. The thesis addresses different aspects of the regional political reality, as: the essential characteristics of the instances of municipal power, the social composition of local political elite, the extension of electoral participation and the meaning of elections, the role of the press and other institutions on political game, the main themes on debate. This work also intends to confront the political reality of the Valley with theory interpretation lines ruling on Brazil‟s First Republic, with special interest in research on the validity of the concept of 'Coronelismo' for that context. It was of particular attention, in this regard, the identification and analysis of the levels of competition intra-oligarchic present there.